Jeri Nichols-Park: capstone - Nichols-Park, Jeri, artist (Colorado State University. Libraries, 2014)
The artist's statement: Having experimented with many media, techniques, and materials, my art has continued to evolve over many years. My "go-to" tool has always been pencil, easy to use, easy to erase, easy to make changes. Always my work starts out as an idea translated into a sketch, and then it goes from there - could be watercolor, pastel, pen and ink, or a combination, and I have done many drawings, portraits, paintings, and prints over many years. But more recently I find myself creating unique fabrics by hand-painting silk, dyeing, printing, and weaving. Some end up as wall pieces, but more often than not they become a jacket, hat, skirt, scarf, or a blouse. I have designed apparel professionally for many years, but now feel like I am taking it to the next level by creating the fabrics they are made from. I see my one-of-a-kind garments as an art unto themselves...another artistic expression of myself. Rarely does a day go by when I am not thinking about what I will do next, as I am always inspired by medium I will use. When I am drawing, painting, or weaving, I become totally immersed in my work, allowing my emotions and subconscious mind to direct the process. At the start of a project I have an idea of what I mean to create and set about the task with intention, but I find when I let my "inner artist" take over the end result is almost always so much better than what I envisioned. I believe that art is as unique as the artist, the expression of each individual's unique experiences and emotions. Over the years I have finally learned that it's fruitless and self-destructive to compare my art to others; I am where I need to be, on my own path, as we all are. I create and work at my own pace and believe that true creativity cannot be forced. I want my work to be recognizable as "mine"; that viewers will know by the style, techniques, and subject matter that I am the artist. More than that I want people to know that my work is genuine, that it was well thought out, and is a true expression of me.
Colorado State University Art Department capstone project.
Capstone contains the artist's list and images of works.
Keywords: fibers